2021
DOI: 10.3389/fnbeh.2020.620119
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Cholinesterase Inhibitors as Antidepressants? Dose and Stress-Sensitivity May Be Critical to Opening Possibilities

Abstract: When stress becomes chronic it can trigger lasting brain and behavioral changes including Major Depressive Disorder (MDD). There is conflicting evidence regarding whether acetylcholinesterase inhibitors (AChEIs) may have antidepressant properties. In a recent publication, we demonstrated a strong dose-dependency of the effect of AChEIs on antidepressant-related behavior in the mouse forced swim test: whereas the AChEI donepezil indeed promotes depression-like behavior at a high dose, it has antidepressant-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…It is implied that lower doses of drugs can safely be used to treat depression such as YG and ES. Previous research showed that the therapeutic effects of a low dose of antidepressants merely disappeared, instead of becoming aversive or toxic ( Fitzgerald et al, 2020 ). However, chronic treatment with antidepressants was more popular.…”
Section: Discussionmentioning
confidence: 99%
“…It is implied that lower doses of drugs can safely be used to treat depression such as YG and ES. Previous research showed that the therapeutic effects of a low dose of antidepressants merely disappeared, instead of becoming aversive or toxic ( Fitzgerald et al, 2020 ). However, chronic treatment with antidepressants was more popular.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the commonly used AChE inhibitors show a dose-dependent response, as previously mentioned. It is suggested that their use in the treatment of depression is also associated with a dose-dependent response [328]. Researchers suggested that these inhibitors induce antidepressant efficacy only at lower doses.…”
Section: The Use Of Ache Inhibitors For Mdd and Bpadmentioning
confidence: 99%
“…Moreover, in a case report by Lim et al, the antidepressant effect of donepezil at a dose of 5 mg as adjunctive therapy was noticed in a 62-year-old woman with a history of depression without any cognitive problems whose depression was resistant to routine depression treatments and even nextline drugs (82). However, as previously stated, some studies have shown inconsistent evidence regarding donepezil's efficacy in treating depression (80,83). Reynolds et al, for example, in a clinical trial study, found that donepezil was ineffective in treating depression in 130 older adults with depression and mild cognitive impairment (38).…”
Section: Mood Disordersmentioning
confidence: 97%
“…Donepezil and AChEIs have shown mood-modifying properties in animal and clinical trials. However, some research has refuted this efficacy, and the findings of specific studies have shown that these medicines cause depression, mania, or even exacerbation of the underlying condition (13,80). In an animal study by Papp et al, using 96 rats in both stress and control groups, the anxiolytic, antidepressant, and cognitive-improving effects of donepezil (0.3 mg/kg intraperitoneally), rivastigmine, imipramine, and memantine were investigated.…”
Section: Mood Disordersmentioning
confidence: 99%